Modification of Adenovirus vaccine vector-induced immune responses by expression of a signalling molecule - Rollier, CS; Spencer, AJ; Sogaard, KC; Honeycutt, J; Furze, J; Bregu, M; Gilbert, SC; Wyllie, D; Hill, AVS (Springer Nature, 2020)
Adenoviral vectors are being developed as vaccines against infectious agents and tumour-associated antigens, because of their ability to induce cellular immunity. However, the protection afforded in animal models has not easily translated into primates and clinical trials, underlying the need for improving adenoviral vaccines-induced immunogenicity. A Toll-like receptor signalling molecule, TRAM, was assessed for its ability to modify the immune responses induced by an adenovirus-based vaccine. Different adenovirus vectors either expressing TRAM alone or co-expressing TRAM along with a model antigen were constructed. The modification of T-cell and antibody responses induced by TRAM was assessed in vivo in mice and in primates. Co-expression of TRAM and an antigen from adenoviruses increased the transgene-specific CD8+ T cell responses in mice. Similar effects were seen when a TRAM expressing virus was co-administered with the antigen-expressing adenovirus. However, in primate studies, co-administration of a TRAM expressing adenovirus with a vaccine expressing the ME-TRAP malaria antigen had no significant effect on the immune responses. While these results support the idea that modification of innate immune signalling by genetic vectors modifies immunogenicity, they also emphasise the difficulty in generalising results from rodents into primates, where the regulatory pathway may be different to that in mice.